A Interação das Marcas com o Público através do Facebook: O Mercado dos Smartphones e as Marcas Samsung e Apple. - Pintor, Simão (2014)
Social networks, and Facebook in particular, play a huge role for brands in the time being, since they are a powerful vehicle for them to interact with their customers and potential customers. A single post done through a computer, tablet or smartphone can reach millions of people in a very short time.Therefore, it is essential to understand the importance for brands of investing in the management of this interaction, ascertaining its impact on brand awareness and brand loyalty.For this purpose, a questionnaire survey was applied to some users of this social network. Considering the measurement of the variables “brand awareness” and “brand loyalty”, the survey was restricted to the market of smartphones, and to the brands Samsung and Apple, which have distinct policies considering the management of their social networks. There were 209 collected answers, and the sampling process was non-probabilistic by convenience, so there is no guarantee that the sample is representative of the population in study.After the analysis of the collected data, it can be said that there is statistical evidence which shows that, for the sample concerned, there is a positive relationship between the brands’ interaction in Facebook and their brand awareness. On the other hand, the results showed that, for this sample, there was no relationship between that interaction and brand loyalty. These assumptions may indicate that brands should invest in this process shall the increase of their awareness be an important goal for them.